Comparative Analysis of Project Management Software: Functionality, Usability, and Integration for Modern Workflows - Md Alamgir Miah (Journal of Informatics Education and Research, 2025)
This research aims at determining the suitability of the trending PM tools; Microsoft Project, Jira, Trello, and Asana based on the functionality, security, usability and cost needs of different organisations. The study reveals that while Microsoft Project and Jira offer better-developed features, their complexity and cost make them more suitable for large companies. On the other hand, Trello and Asana have simple and easy to use interface, which is suitable for small and medium sized business and also they are less costly, but they lack the depth of features and security features which may be required by some large companies or companies in some highly regulated industries. In addition, the study reveals an increasing interest in flexible PM tools that support different methodologies and have security measures to meet the data protection challenges of cloud projects. The results of this study imply that PM tool selection criteria should be matched to particular organisational capability, weighing utility, security, and cost. The study also suggests new tendencies concerning further developments such as the demand for PM solutions that are suitable for Agile and Waterfall methodologies concurrently, as well as the need for more elastic pricing strategies.